IMPROVING RICE YIELD AND INCOME OF FARMERS BY MANGING THE SOIL ORGANIC CARBON IN SOUTH SUMATRA LANDSCAPE, INDONESIA - Armanto, M. E. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The research aimed to improve rice yield and income of farmers by managing the soil organic carbon to achieve food security in South Sumatra landscape. This research has been done in agricultural land of Ogan Komering Ilir (OKI) District, South Sumatra. This research is an experimental research by using completely randomized design in factorial. The first factor was rice variety (local and superior), and the second factor was six ricefields, namely ricefields of sandy rainfed; loamy rainfed; lebak (freshwater swamp); tidal swamp; and technical irrigation. Composite soil samples were taken from each ricefield and analyzed in the laboratory for organic C content. Rice production data were collected by quadratic methods measuring 5x5 m. The research resulted that the SOC can increase the soil productivity, if the soil productivity can be increased, then the rice yield also increases and the consequences income of household also increases linearly. The contribution of the SOC contents in the rooting areas is able to improve the soil productivity, especially for soils having the following characteristics: coarse and sandy textures, lower SOC contents, receiving lower chemical fertilizer, managed under rainfed conditions rather than irrigation, and poor soils rather than good quality of soils.